Ischemic Stroke and its Association with Risk Factors at Nepalgunj Medical College Teaching Hospital Kohalpur - BK, Shyam Kumar; Baral, Sushil; Paudel, Nabin; Neupane, Hitesh (Journal of Nepalgunj Medical College, 2021)
Introduction: Incidence of stroke increases with age and growing elderly population worldwide, the number of patients with stroke are likely to increase. It is the third most common cause of death in world in that 85% are ischemic in nature. Atherosclerosis is a major risk factor in cerebrovascular diseases. Carotid Intima Media thickness (CIMT) is a surrogate marker of atherosclerosis and provides a non-invasive method for the risk assessment of cerebrovascular diseases. Aims: To study the atherosclerotic risk profile of patients admitted with ischemic stroke in medical ward with study of the carotid artery intima-media thickness in patients with acute ischemic stroke. Methods: 92 patients with ischemic strokes were studied in this observational study. Carotid Doppler was performed in all patients with emphasis on carotid artery stenosis and intima thickening. Analysis of Association of various risk factors was done in detail. Study period was from June 2019 to May 2020. Results: Higher degree of stenosis was associated with hypoechoic plaques and cortical strokes. Hypertension was the most common and most significant risk factor. Multiple risk factors also appear to have synergistic actions. Conclusion: Various modifiable risk factors provide valuable target for primary and secondary prevention of stroke. Carotid Doppler is a very cheap and highly effective tool for further management of stroke patients. Most of the asymptomatic patients, risk factors may warrant precautionary carotid Doppler, and may result in significant reduction in disease burden on the families and the community and should be encouraged.